Telomere Interacting Proteins and TERRA Regulation - Pérez-Martínez, Lara; Wagner, Tina; Luke, Brian (Frontiers in Genetics, 2022)
Telomere shortening rates inversely correlate with life expectancy and hence it is critical to understand how telomere shortening is regulated. We have recently implicated the telomeric non-coding RNA, TERRA in regulating replicative senescence. To better understand how TERRA is regulated we employed a proteomics approach to look for potential RNA regulators that associate with telomeric sequences. Based on the results we have identified proteins that may regulate TERRA in both a positive and negative manner, depending on the state of the telomere.